Pengaruh Profitabilitas, Leverage, dan Umur Perusahaan terhadap Ketepatan Waktu Penyampaian Laporan Keuangan pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2019 - 2022 - Lisa Surya Lestari; Setiyo Purwanto (Strata Business Review, 2023)
This study aims to examine the effect of profitability, leverage and company age on the timeliness of financial reporting for manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2022 period. Leverage, which is assessed using the Debt to debt-equity ratio (DER), and firm age, which is measured using the difference between the date of the observation period and the date of establishment, are the elements examined in this study. Return on assets (ROA) is the metric used to quantify profitability. Quantitative research is the type of research that is included here. The data collection for this study uses secondary data, which is presented in the form of financial reports from companies. The sample in this study used a purposive sampling method to produce 148 observations from 37 companies according to predetermined criteria. The analytical method in this study was tested using the SmartPLS program. The results showed that profitability had no significant effect on the timeliness of financial reporting, leverage had a significant negative effect on the timeliness of financial reporting and firm age had a significant positive effect on the timeliness of financial reporting in manufacturing companies.